Motivational Atmosphere and Moral Behavior as Indicators of Coaching Effectiveness - Alonzo L Mortejo; Jesselyn Mortejo (Performa, 2022)
Study Purpose. The perceptions of coaches' moral character and the factors that make a successful coaching environment were the main subjects of this study. Materials and Methods. Utilizing a descriptive survey approach, the investigation was finished. Experienced collegiate coaches from various sports leagues at preselected public schools and universities were included in the study.. Results and Discussions. According to data, university sports programs should place a high priority on coaches' moral behavior, particularly when it comes to treating players fairly and carrying out their tasks without violating their rights based on their race, gender, or other characteristics. Coaches should also provide each athlete equal attention and create a motivating environment for them. Conclussion. Better policy in collegiate sports programs should be built on more research on the effectiveness of coaches.